Association Between Serum Infliximab Trough Concentrations During Maintenance Therapy and Biochemical, Endoscopic, and Histologic Remission in Crohn's Disease. Issue 10 (28th April 2018) - Papamichael, Konstantinos; Rakowsky, Shana; Rivera, Claudio; Cheifetz, Adam S; Osterman, Mark T
Abstract: Background and aim: Objective and more rigorous therapeutic outcomes are emerging as novel targets in Crohn's disease (CD). We investigated the association between maintenance serum infliximab trough concentrations and biochemical, endoscopic, or histologic remission in CD. Methods: This retrospective multicenter study involved consecutive CD patients treated with infliximab who had a serum C-reactive protein (CRP) measured within 1 week or endoscopic evaluation within 12 weeks of therapeutic drug monitoring between January 2010 and June 2016. Biochemical remission was defined as a normal CRP (≤5 mg/L). Endoscopic remission was defined as absence of any mucosal break (ulceration or erosion) or for patients with an ileocolonic resection, a Rutgeerts score of ≤i1. Histologic remission was defined as absence of active inflammation. Results: Seventy-one CRP levels and 96 colonoscopies from 110 CD patients were evaluated. Based on ROC analyses, infliximab concentration thresholds of 2.2, 9.7, and 9.8 μg/mL were found to be related with biochemical, endoscopic, and histologic remission, respectively. Multiple logistic regression analyses identified infliximab concentration ≥2.2 (OR 6.4; 95% CI, 1.5–27.1; P = 0.011), ≥9.7 (OR 3.6; 95% CI, 1.4–9; P = 0.006) and ≥9.8 μg/mL (OR 3.2; 95% CI, 1.3–7.9; P = 0.011) as variables independently associated with biochemical, endoscopic, and histologic remission, respectively. Conclusions: This study showed that higher maintenance infliximab trough concentrations are associated with more favorable rates of biochemical, endoscopic, or histologic remission in CD patients and that infliximab concentrations may differ based on the treatment goal.